Retraction of "Project work in CLIL: A bibliographical review" - Carl Edlund Anderson (Universidad de La Sabana, 2016)
The article "Project work in CLIL: A bibliographical review" has been retracted at the request of the authorities of the Universidad Católica San Antonio de Murcia (Murcia, Spain) as the manuscript was found to a substantial amount of content derived without credit or citation from the unpublished work of researchers at that institution.